Downregulation of E‐cadherin immunohistochemical expression - Highlights its role in epithelial- to-mesenchymal transition in breast carcinomas - Mohammad Adil; Kafil Akhtar; Mazhar Fahim; Shahid Ali Siddiqui (Annals of Oncology Research and Therapy, 2023)
BACKGROUND: E-cadherin is known to have an important role in the regulation of epithelial–mesenchymal transition process and in the tumor progression. AIMS AND OBJECTIVES: The aim was to study the expression of immunomarker E-cadherin and evaluate its diagnostic and prognostic significance in breast carcinoma. MATERIALS AND METHODS: This prospective study was conducted on 90 diagnosed cases of breast carcinoma presenting clinically with breast lumps. Immunohistochemistry was performed by E-cadherin antibodies and evaluated. RESULTS: Majority of the cases were seen in the age group of 41–50 years, 32 (35.6%). Most of the patients were postmenopausal females, 53 (59.5%). The most common subtype involved was invasive carcinoma No special type (NST) in 78 (86.7%) with Grade 2 in 55 (70.5%) cases. E-cadherin expression was strong in Grade 1 tumors, mixed intensity in Grade 2 tumors, and weak in Grade 3 tumors. Of 11 cases of metastasis, 8 (72.7%) cases showed 1+ E-cadherin immunoexpression and 3 (27.3%) cases showed 2+ immunoexpression. The statistical correlation between E-cadherin immunoexpression with tumor recurrence and distant metastasis was found to be significant (P < 0.001). CONCLUSIONS: Patients with moderate-to-high expression of E-cadherin had a longer disease-free survival. High grade and advanced stage of carcinoma had absent or weak expression of E-cadherin and was associated with aggressive tumor characteristics with early recurrence, distant metastasis, and reduced disease-free survival.